Anatomical and histological description of the digestive tract of the sabaleta (Brycon henni), Antioquia, Colombia - Londoño-Franco, Luis F. (2017)
The present study describes the anatomical and histological pattern of the digestive system of the ‘sabaleta’ (Brycon henni). Six adult male and female individuals were fished in Guaracu creek, Antioquia, Colombia, between May and June 2016. The fish weighed 151.2 g and were 22.7 cm in total length. The organs of the digestive system were fixed in 10% buffered formalin and processed with routine histological techniques. The most remarkable structures, due to their specific anatomical pattern and histological complexity, were the gill rakers (4), the pyloric caeca (13 in females and 8 in males), the bulky and lobate hepato-pancreas, and the anterior, middle and posterior intestine with villi and microvilli. The ‘sabaleta’, according to the digestive pattern as to teeth, gill rakers, stomach, and intestinal structure and length, suggests that it is a kind of omnivorous food habit species, but with a carnivorous tendency.